P–086 High level of sperm DNA breaks in infertile men with varicocele: its association with sperm cells death, seminal oxidative stress, and spermatic parameters. (6th August 2021) - Ammar, O; Mehdi, M
Abstract: Study question: Our objectives were to determine the extent of nuclear sperm injury in varicocele patients with and without altered spermatic parameters and to investigate its relationship with apoptosis and oxidative stress. Summary answer: Oxidative stress (OS) in the varicocele patients may play a role in the etiology of nuclear sperm DNA damage associated with apoptosis. What is known already: Varicocele is associated with high level of DNA Breaks. Study design, size, duration: Ejaculated sperm samples from 51 patients diagnosed with varicocele and 29 fertile men were examined. According to the guidelines, the patient's sperm samples were classified into varicocele with normal semen parameters (n = 11) and varicocele with abnormal semen parameters (n = 40). Participants/materials, setting, methods: Sperm DNA breaks was assessed using terminal deoxynucleotidyl transferase dUTP nick end labeling assay. The proportion of both viable and dead spermatozoa with externalized phosphatidylserine was detected by the bivariate annexin V cy3/6-CFDA staining method. Seminal malondialdehyde (MDA) amounts and antioxidant enzymes activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) were measured spectrophotometrically. Main results and the role of chance: Sperm DNA Breaks, viable spermatozoa with externalized PS, and MDA levels were significantly higher in studied subgroups of patients with varicocele, either with normal or with abnormal semen parameters than controls. The seminal antioxidant enzymes activities were significantly reduced in both subgroups of patients with varicocele compared to the controls. The percentage of spermatozoa with fragmented DNA was positively correlated to the MDA level as well as the proportion of viable spermatozoa with externalized PS. However, the decreased seminal antioxidant status was negatively correlated with the increased proportion of sperm DNA fragmentation and apoptotic spermatozoa. Limitations, reasons for caution: We suggest further comparative studies connecting the varicocele patients with and without altered spermatic parameters representing high level of DNA fragmentation with more apoptotic and oxidative stress markers. Wider implications of the findings: This study reveals that impaired seminal antioxidant profile and increased seminal level of lipid peroxidation may be involved in the pathophysiological mechanisms of cell death-mediated DNA breaks in patients with varicocele. Trial registration number: Not applicable